2020
DOI: 10.1002/chem.201905866
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Synthesis of Janus Fluorographene Derivatives

Abstract: Fluorographene, at wo-dimensional derivativeo f graphene, is an excellent starting materialf or the synthesis of graphene derivatives. In this work, ao ne-step, substratefree method for the asymmetricf unctionalization of fluorographene layers with hydroxyl groups by af acile nucleophilic substitution reactioni sr eported. Such ac hemical modification occurs in ab iphasic aqueous-organic system under mild conditions, leading to Janus graphene nanosheets functionalized by hydroxyl groups on one side and retaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…The obtained bifunctional product exhibited entirely different self-assembly behaviors in various solvents. [82] In conclusion, by taking advantage of the unique functional chemistry of FG, specific functional groups are designed to be grafted onto the graphene surface, which opens a universal route for the functionalization and even multifunctionalization of graphene, which further expands its application fields. In addition, the generality of its derivative chemistry for some other classical organic reactions has been verified.…”
Section: Lai Et Al Developed the Friedel-crafts Reaction Between Fgmentioning
confidence: 99%
See 3 more Smart Citations
“…The obtained bifunctional product exhibited entirely different self-assembly behaviors in various solvents. [82] In conclusion, by taking advantage of the unique functional chemistry of FG, specific functional groups are designed to be grafted onto the graphene surface, which opens a universal route for the functionalization and even multifunctionalization of graphene, which further expands its application fields. In addition, the generality of its derivative chemistry for some other classical organic reactions has been verified.…”
Section: Lai Et Al Developed the Friedel-crafts Reaction Between Fgmentioning
confidence: 99%
“…On the basis of derivative reactions of FG, it is toilless to directly prepare multifunctional graphene-based materials and expand the applications of FG. [77][78][79]82,83,[258][259][260] Similar to the structure engineering of CF bonds in FG sheets, the structure engineering based on the derivative reaction of FG is also one of the important strategy to optimize the structure and the corresponding performance, such as controlling the modified region of the FG derivatives. Otyepka et al found that the CF bonds of FG increase the polarity of surrounding aromatic regions and facilitated the photo-induced cyclization reaction.…”
Section: Derivative Reaction Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] In particular, signicant effort has been devoted to engineer a band gap in graphene by introducing structural defects 5 or by surface functionalization with H or F atoms. 6,7 Aer covering graphene with heteroatoms, the band gap is opened due to the transformation of sp 2 -hybridized carbon into sp 3 hybridized carbon. In contrast to graphene, hydrogenated graphene exhibits uorescence, 8 paramagnetism, 9 fast heterogeneous electron transfer, 10 and tunable band gap (0-3.7 eV).…”
Section: Introductionmentioning
confidence: 99%